Optimized RC timing technique for accurate measurement of minute capacitance changes - Zaharudin, Zarimin; Adam, Ismail; Abdul Kadir, Kushsairy; Khan, Sheroz; Nordin, Anis Nurashikin; Ahmed Shaikh, Faraz; Hassan Abdalla Hashim, Aisha; Abdul Malik, Noreha; Wan Morshidi, Wan Hafiy (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper presents a technique for accurate measurement of small capacitive changes. This is based on selecting the most linear part of the curve obtained by charging the capacitor undergoing changes through a known resistor value. This measurement is part of the design of a system for measuring blood glucose content non-invasively. The technique is based on measuring ultra-low low glucose levels in the blood as capacitive changes converted into RC timing constant optimized using a circuit set to trigger at an appropriate time activating a counter. The measured data is captured instant later, selecting the most linear part of the charging curve. The results so obtained are compared with the ones obtained through RC-timing standard procedure. The technique reported is with a remarkable low error of about 2.25% as against 11.78% by the standard RC-timing technique.